Nutrient management in clove (Syzigium aromaticum L.) for sustainable production - M Jayasekhar, R Swarna Piria (Journal of Spices and Aromatic Crops, 2008)
An experiment was carried out to formulated nutrient management for sustainable productionon 10 year old trees of clove. Both organic and NPK fertilizers were used in 6 combinations.Though no marked difference between treatments were observed the combination of 5 kg ofvermicompost, 150:300:900 g NPK and a foliar spray of 2% panchkavya recorded the highestyield